CAP reform progress - Miron Dumitrescu; Şerban Tăranu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
CAP reform is an opportunity for the EU and the new member states to make progress in terms of protecting peasant agriculture and farmers themselves in developing Europe's future. This requires reform of the Common Agricultural Policy as a necessity for the new Member States. They need to establish a set of clear objectives for sustainable development of the agricultural sector and also methods for a more efficient implementation of the common policy. This article follows a description of the CAP reform. While EU countries are developed, showcasing a stable economy, agricultural production and prices of agricultural products are influenced by favorable or unfavorable weather conditions. The new Member States have to find ways of solving old problems of agriculture, but also to meet the new challenges of European integration.
Keywords: 330; economic reform; sustainable agriculture; eligible prices